2008
DOI: 10.1097/tp.0b013e31818bd96f
|View full text |Cite
|
Sign up to set email alerts
|

Inhibition of Humoral Response to Allogeneic Porcine Mesenchymal Stem Cell With 12 Days of Tacrolimus

Abstract: Immunosuppressive drugs significantly affect proliferation and viability of MSCs, but neither TAC nor SIR had a detrimental impact on MSCs' immunomodulatory properties. In this large-animal model, addition of short course of immunosuppression seems to overcome the immune response to intracardiac allogeneic MSCs, which was recently demonstrated to occur in the absence of immunosuppression.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
17
0

Year Published

2010
2010
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 21 publications
(18 citation statements)
references
References 57 publications
1
17
0
Order By: Relevance
“…The antibody surge in our study occurred rapidly (within 5 days) and accompanied the strong cellular immune activation. Reports that short-term T-cell-specific immunosuppression prevented the antibody response against transplanted MSCs support the hypothesis of a T-cell-driven humoral response against cellular grafts (Poncelet et al, 2008). Ongoing humoral rejection of islet grafts was successfully treated with an anti-CD20 monoclonal antibody (Kessler et al, 2009).…”
Section: Discussionmentioning
confidence: 71%
“…The antibody surge in our study occurred rapidly (within 5 days) and accompanied the strong cellular immune activation. Reports that short-term T-cell-specific immunosuppression prevented the antibody response against transplanted MSCs support the hypothesis of a T-cell-driven humoral response against cellular grafts (Poncelet et al, 2008). Ongoing humoral rejection of islet grafts was successfully treated with an anti-CD20 monoclonal antibody (Kessler et al, 2009).…”
Section: Discussionmentioning
confidence: 71%
“…Second, it is of interest to know whether immunosuppressive therapies currently prescribed in organ transplantation can be effectively used to prevent anti-donor immune responses to alloMSCs in vivo without diminishing therapeutic efficacy. In this regard, Poncelet et al (2008) have shown, in a miniature pig model of myocardial infarction, that the calcineurin inhibitor tacrolimus significantly attenuated the anti-donor antibody response to allo-MSCs delivered directly into the infarct. Recently, Ge et al (2009) also demonstrated that a combination of allo-MSC infusion and low-dose sirolimus (rapamycin) therapy resulted in long-term survival of fully MHC-mismatched heart transplants in mice.…”
Section: To What Extent Are Allo-mscs Immunoprivilegedmentioning
confidence: 99%
“…Based on our previous work on tolerance after allogeneic full organ transplantation [13] as well as on our most recent experimental work demonstrating that with a moderate transient immunosuppression, the primary immune response to allogeneic MSC transplantation could be overcome [14], we decided to use in the present study a 12-day course of tacrolimus.…”
Section: Introductionmentioning
confidence: 99%